Solvent degradation studies using hydrodynamic cavitation - Suryawanshi, Pravin G.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ruparelia, Jayesh P.; Ranade, Vivek V. (Environmental Progress & Sustainable Energy, 2018)
Hydrodynamic cavitation for the degradation of organic solvents was investigated in detail using a newer form of cavitating device-vortex diode. The results were also compared with that using conventional cavitating device orifice. Removal of three different organic solventsacetone, methyl ethyl ketone (MEK), and toluene were studied on a pilot plant with capacity of 1m(3)/h. The effect of different operating parameters such as inlet pressure, initial concentration, and reactor type on the degradation rate of solvent was investigated in detail. The results revealed that efficiency of solvent removal varies substantially with the change in physical operating conditions and nature of the solvent. It was found that up to 80% degradation could be achieved for toluene (cavitational yield 32.2 x 10(-3) mg/J), substantially higher than that for acetone and MEK indicating the effect of molecular weight/structure in the degradation process. Further, the results clearly indicated chemical oxidation as a predominant mechanism for degradation and not physical destruction. Vortex diode that works on the principle of vortex generation for cavitation, was found to be far superior over conventional cavitating device-orifice- approximate to up to eight times higher cavitational yield could be obtained for toluene as compared to orifice. The results of this study provide newer insight into solvent removal using hydrodynamic cavitation and would have bearing on the treatment of solvent containing wastewaters. (C) 2017 American Institute of Chemical Engineers
Keywords: Effluent treatment; industry; pollution; Vortex diode; wastewater

Safe water and technology initiative for water disinfection: application of natural plant derived materials - Mane, Maya B.; Bhandari, Vinay M.; Ranade, Vivek V. (Journal of Water Process Engineering, 2021)
Safe drinking water is the necessity of life. The present study reveals use of natural resources such as plant extracts and natural oils for water disinfection. Differences between oil and water soluble additives were highlighted for plant extracts and insoluble natural oils. A hybrid hydrodynamic cavitation process was quite effective in both the cases and high rates of disinfection were achieved. Studies were reported using oils (ginger, turmeric, lavender, tulsi) and rhizome derived plant extracts such as ginger, turmeric and mango ginger, as additives in process intensification (0.1% v/V). A vortex based cavitation device (vortex diode, nominal capacity 1 m3/h) was used with pressure drop of 1 bar. A high disinfection of 96% and 88% was obtained in 15 min for ginger oil and mango ginger extract respectively as compared to 44% using cavitation alone. Acoustic cavitation gave 94% and 30% disinfection with and without additive-mango ginger extract. The FTIR analyses before and after cavitation, with ginger additive, showed no by-products formation and indicated gingerol as active component in disinfection. The per-pass disinfection values were also higher, up to 5 times than cavitation alone. Hybrid hydrodynamic cavitation using natural plant derived materials can offer a promising technology alternative in water disinfection.
Keywords: Cavitation; Disinfection; Natural oil; Plant extract; Water treatment

Solvent-assisted cavitation for enhanced removal of organic pollutants - degradation of 4-aminophenol - Patil, Pravin B.; Bhandari, Vinay M. (Journal of Environmental Management, 2022)
A new approach of solvent-assisted cavitation process was proposed for degradation of organic pollutants. The process envisages the use of suitable solvent as an additive, (1-5% v/V), in the conventional cavitation process to enhance the pollutant removal efficiency. A proof of concept was provided for the removal of ammoniacal nitrogen with significantly improved efficiency using solvent-assisted hydrodynamic cavitation (HC) compared to conventional HC. The efficacy of the process was studied on a pilot plant scale (1 m(3)/h) and using vortex flow based vortex diode as a cavitating device. Degradation studies were carried out using a model pollutant, 4-amino phenol and four different solvents as additives, 1-octanol, cyclohexanol, 1-octane and toluene. Relatively polar solvents were found to increase the efficiency of the pollutant removal (> 65%) and also increase the rates to an extent of more than 200%, compared to only HC. A very high removal of ammoniacal nitrogen, more than 90%, was obtained for solvents 1-octanol and cyclohexanol, indicating the importance of the selection of solvent. Per pass degradation model showed 3 to 4 times increase in the per pass degradation for polar solvents compared to cavitation alone. The results confirm no role of conventional solvent extraction and no specific contamination of wastewater due to the use of solvent as an additive in the process. Further, the cost was 2-3 times lower as compared to the conventional HC. The interesting observations in the proposed process can fuel further research to provide possible improvements in existing methodologies of wastewater treatment, in general, and for removal of ammoniacal nitrogen, in particular.
Keywords: Ammoniacal nitrogen; Hydrodynamic cavitation; Oxidation; Pollution Control; Wastewater treatment

Studies in instant water disinfection using natural oils - Dixit, Divya; Bhandari, Vinay M.; Mane, Maya B.; Balapure, Kshama (Biochemical Engineering Journal, 2022)
The present research reveals an instant and simple process for drinking water treatment by employing specific natural oils having antimicrobial properties to ensure complete elimination of harmful bacteria. The disinfection was studied for two different model bacteria, Gram-negative E. coli and Gram-positive, S. aureus. Seven natural oils, ajwain, thyme, oregano, peppermint, harsingar, cinnamon leaf and black pepper oil were evaluated and were found to yield 100% water disinfection within 1 min except for harsingar and black pepper oil. The process was also effective for the instant and 100% disinfection of real well water. The methodology for altering zeta potential, to an extent of 130%, for instant disinfection in drinking water treatment helps in selecting natural oils. Molecular docking studies indicated natural oils action as potential inhibitors of bacterial DNA gyrase. The studies indicate one of the lowest operating costs comparable to conventional chlorination. The simple meth-odology not requiring complex equipment has the potential to provide many options for implementations-from portability, household application to large scale water treatment plants.
Keywords: Bacteria removal; Natural oil; Technology; Water treatment; Zeta potential

Sustainable fabrication of copper nanoparticles: a potent and affordable candidate for water treatment, water disinfection, antioxidant activity and theranostic agent - Sinha, Tanur; Adhikari, Partha Pradip; Bhandari, Vinay M. (ChemistrySelect, 2022)
This study reports a simple, green, and large-scale biosynthetic fabrication of spherical copper nanoparticles (Cu NPs), approximate 28 nm, using the aqueous extracts of Diaplazium esulentum (Retz.) Sw. fern. Characterization was carried out for morphology, size, elemental analysis, crystallinity and for identification of functionalities responsible for reduction and stabilization. Extraordinary remediation efficiency was obtained for the developed Cu NPs for the elimination of two industrially important pollutants; Methyl Violet 6B and Methylene Blue (greater than 92 % within 150 mins). A mechanism was postulated for the process using the data on the identification of NPs and also spent NPs apart from degraded products. Furthermore, the Cu NPs revealed excellent antibacterial activity against gram positive bacteria: Staphylococcus aureus, Streptococcus pneumonia and Bacillus subtilis, as well as gram negative bacteria: Pseudomonas aeruginosa, Escherichia coli and potential action against fungal strains; Aspergillus niger and Candida albicans. Additionally, the assay depicted that Cu NPs has fairly decent radical scavenging activity with IC50 value 2.11 mM. Moreover, the Cu NPs were found to exhibit profound anticancerous activity against two human cancer line cells. The present research work has implications for exploitation of DE fern extract for the development of Cu NPs and their numerous applications ranging from pollutants removal to antibacterial, antifungal, antioxidant and anticancerous agents.
Keywords: Anticancer; antifungal; Antimicrobial; Antioxidant; Photodegradation and Phytosynthesis